Use of Boyle's Law Apparatus in Boyle's Law Practicum: A Cookbook Model Approach to Apparatus Testing and School Implementation - Dewi Salsabila, Luthfiah; Malik, Adam (Prodi Fisika FKIP Unram, 2024)
This study aims to evaluate the effectiveness of Boyle's Law Apparatus in teaching the relationship between pressure and volume of gas at constant temperature, utilizing a structured cookbook practicum approach. An experimental method was employed at MA Alinayah Bandung, involving four variations of pressure and ten trials for each variation, resulting in a total of 40 trials. The tools used included vacuum tubes, vacuum pumps, manometers, and volume meters for accurate measurement of pressure and volume. Results demonstrated a consistent inverse relationship between gas volume and pressure, aligning with Boyle's Law, where P Ã— V remained constant. The structured approach facilitated accurate data collection and enhanced students' comprehension of gas behavior principles. The findings highlight the importance of practical experimentation in physics education, providing students with hands-on experience and fostering critical thinking skills for a more interactive learning environment. Keywords: Boyle's Law; Gas Behavior; Experimental Method; Physics Education; Cookbook Practicum.